Media Baru dan Jurnalisme Warga: Sebagai Sumber “Hoax” dan “Black Campaign” pada Agenda Politik - Rafles Abdi Kusuma (Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2019)
This article refers to the current communication issue where the emergence of new media give chance to the creation of a truly, practice of journalism. That is no longer conducted by professional journalists but by ordinary citizens. This writing focus on how the opportunities of new media and its challenges in people journalism and political agenda which using as fact news disseminators (hoax) and source run of black campaign content at both the national and regional political. The Habermas theory of public space where used to seeing new media become more crowded with various, opinion, news and of commentaries about politics. As in the case of seword.com, the news portal site was by a group of unknown writter its non credibility media worker. The use of social media by Bunni Yani who spread a message provocative and SARA in a contestation, political or agenda in the region hoax and black campaign. On the context of contestation or political agenda in the region, hoax and black campaign can break up nation’s unity at the regional level. Even the phenomenon in Jakarta Local Election perceived have influenced political stability and life state in general in Indonesia. In which front new media uses and journalism that they have to more support by participation political public that puts forward ethics journalistic, to unite wholeness the people and the country, instead of divided.